Medical rubber composite material as well as preparation method and application thereof
By using composite materials composed of rubber, polyether ether ketone, hydroxyapatite, etc., rubber medical composite materials with high porosity, high mechanical strength, good biocompatibility and antibacterial properties were prepared, and the existing materials were solved. The shortcomings in mechanical properties, porosity and osteogenic effects have achieved efficient preparation and application of medical materials.
Patent Information
- Application Number
- CN202411548977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The existing rubber aerogel materials have shortcomings in mechanical properties, porosity and osteogenic effects, and it is difficult to meet the needs of medical materials in terms of biocompatibility, antibacteriality and high mechanical strength.
Rubber fibers are prepared by crushing and refining treatment by using composite materials composed of rubber, polyether ether ketone, hydroxyapatite biocompatible agent, bacteriostatic agent and crosslinking agent, and dissolve, stir and freeze-drying by solvent dissolving, stirring and freeze-drying Then prepare rubber medical composite materials.
It realizes the low cost of rubber medical composite materials, simple composition processing, simple preparation method, high porosity, high mechanical strength, good biocompatibility and antibacterial properties, and has good osteogenesis induction effect, suitable for medical materials industrial production.
Smart Images

Figure BDA0005114562860000101 
Figure BDA0005114562860000111 
Figure BDA0005114562860000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical material engineering, and in particular to a rubber medical composite material, a preparation method thereof and an application thereof. Background Art
[0002] With the continuous development of medical technology, the market demand for medical rubber products will continue to grow. In the next few years, the research and development and application of new medical rubber products will become the focus of industry attention, such as wearable medical devices, smart medical devices, etc. At the same time, as the global population aging trend intensifies, the demand for medical rubber products for the elderly will continue to grow. Traditional materials are difficult to use in humans and animals, mainly because of biocompatibility, mechanical properties and fatigue resistance. The soft tissues, bones, skin and other parts of the human body are all flexible, fatigue-resistant and have a certain strength. It is difficult to find a material that can be directly replaced in nature. Rubber composite materials will be a solution to this problem. Rubber has sufficient flexibility, good fatigue resistance and bending resistance, and good mechanical properties.
[0003] For example, patent CN108670505A discloses a 3D printed intervertebral fusion device and its preparation method. The intervertebral fusion device is made of polyaryletherketone series materials as the basic raw material and a mixture of degradable polymer materials and osteogenic active powder as the auxiliary raw material through double nozzle extrusion 3D printing technology. The intervertebral fusion device has a hollow three-dimensional interconnected structure, wherein the volume ratio of the basic raw material to the auxiliary raw material is 1:0.01-1:1. From this patent, it can be learned that polyetheretherketone (PEEK) has become one of the most promising artificial bone matrix composite materials due to its excellent wear resistance, biocompatibility, chemical stability and other advantages.
[0004] Studies have shown that with the addition of PEEK, its in vitro biocompatibility gradually increases. As an aerogel material, it has the characteristics of high porosity, low density, good load-bearing capacity, and high deformation resistance, and has incomparable advantages compared with other materials. PEEK itself has high tensile strength, modulus, and wear resistance. Adding it to rubber-based aerogel can significantly enhance the strength, stiffness, and performance of the composite material. This makes the composite material more stable when subjected to external forces and less prone to deformation or damage. Hydroxyapatite (HAP) is the main inorganic component of human bones and teeth. It has excellent biocompatibility, bioactivity, and osteoconductivity and is an important bone repair material. The combination of polyetheretherketone and hydroxyapatite can significantly enhance the biocompatibility and osteogenicity of rubber-based aerogel. Magnesium ions have an osteogenic induction effect, which can stimulate the proliferation and differentiation of bone cells and promote the formation of new bones. After combining with PEEK, its biocompatibility and antibacterial properties can be significantly enhanced. This osteogenic induction effect may be better exerted, which helps to accelerate the repair and healing process of bone defects.
[0005] For example, patent CN115350334B discloses a preparation method, product and application of a polyimide-based composite aerogel material. In terms of mass fractions, the polyimide-based composite material is composed of the following components: 80-100 parts of polyimide, 0-12 parts of polyether ...
[0006] Rubber composites, especially medical silicone rubber, have excellent biocompatibility. This means that when they come into contact with human tissue, they will not cause adverse reactions such as rejection, inflammation or carcinogenesis. This property makes rubber composites an ideal material for manufacturing medical products such as artificial organs and medical devices. In addition, rubber composites generally have excellent high and low temperature resistance. For example, silicone rubber can be used for a long time in a wide temperature range of -60℃-200℃, which makes them perform well in medical applications that need to withstand extreme temperature conditions. In addition, silicone rubber also has good air permeability. This is especially important for medical applications that require gas exchange, such as artificial lungs. The selective permeability of silicone rubber films enables it to control the passage of specific gases to meet specific medical needs. However, as an aerogel material, rubber aerogel has the disadvantage of insufficient mechanical properties.
[0007] Therefore, there is an urgent need to develop a rubber medical composite material with low cost, simple component processing, simple preparation method, good mechanical properties, high porosity and good osteogenesis effect. Summary of the invention
[0008] Based on the deficiencies of the prior art, the present invention aims to provide a rubber medical composite material, a preparation method thereof and an application thereof, so as to solve the problems existing in the above-mentioned prior art, so that the aerogel material has low cost, simple component processing, simple preparation method, high porosity, high mechanical strength, and also has good biocompatibility and good osteogenesis effect.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] In one aspect, the present invention provides a rubber medical composite material, which is composed of the following components by weight: 80-100 parts of rubber, 0-12 parts of polyetheretherketone, 0-15 parts of hydroxyapatite biocompatible agent, 0-3 parts of antibacterial agent, and 0.1-0.5 parts of cross-linking agent. Wherein, the polyetheretherketone, hydroxyapatite biocompatible agent and antibacterial agent are not 0 at the same time.
[0011] Preferably, the rubber medical composite material is composed of the following components by weight: 85-95 parts of rubber, 3-8 parts of polyetheretherketone, 3-12 parts of hydroxyapatite biocompatible agent, 0-2 parts of antibacterial agent, and 0.1-0.3 parts of cross-linking agent. Wherein, the polyetheretherketone, hydroxyapatite biocompatible agent and antibacterial agent are not 0 at the same time.
[0012] Further preferably, the rubber medical composite material is composed of the following components by weight: 90-95 parts of rubber, 3-5 parts of polyetheretherketone, 3-7 parts of hydroxyapatite biocompatible agent, 0-1 part of antibacterial agent, and 0.1-0.2 part of cross-linking agent. Wherein, the polyetheretherketone, hydroxyapatite biocompatible agent and antibacterial agent are not 0 at the same time.
[0013] More preferably, the rubber medical composite material is composed of the following components by weight: 92 parts of rubber, 4 parts of polyetheretherketone, 3 parts of hydroxyapatite biocompatible agent, 1 part of antibacterial agent, and 0.1 part of cross-linking agent. Wherein, the polyetheretherketone, hydroxyapatite biocompatible agent and antibacterial agent are not 0 at the same time.
[0014] Preferably, the rubber includes one or more of purified modified natural rubber, medical silicone rubber, polyurethane rubber, and more preferably medical silicone rubber and natural rubber.
[0015] Preferably, the hydroxyapatite biocompatible agent is selected from one or more of hydroxyapatite, alumina composite hydroxyapatite, and calcium alginate composite nano-hydroxyapatite;
[0016] The antibacterial agent is selected from one or more of oxide antibacterial agents, diammonium phosphate inorganic antibacterial agents, acylanilide antibacterial agents, imidazole antibacterial agents, thiazole antibacterial agents, isothiazolone derivative antibacterial agents, quaternary ammonium salt antibacterial agents, biguanide antibacterial agents and phenolic antibacterial agents;
[0017] Preferably, the oxide-based antibacterial agent is selected from one or more of nano magnesium oxide, nano zinc oxide, nano copper oxide, nano titanium oxide, nano silver oxide, zinc oxide and copper oxide.
[0018] Preferably, the acylanilide antibacterial agent is selected from one or more of nicotinamide, thiothiophene, flutolanil and metalaxyl.
[0019] Preferably, the imidazole antibacterial agent is selected from one or more of clotrimazole, ketoconazole and miconazole.
[0020] Preferably, the thiazole antibacterial agent is selected from one or more of thiazole zinc and ethaboxam.
[0021] Preferably, the isothiazolone derivative antibacterial agent is selected from one or more of methylisothiazolinone (MIT), octylisothiazolinone (OIT), and 5-chloro-2-methylisothiazolin-3-one (CMIT).
[0022] Preferably, the quaternary ammonium salt antibacterial agent is selected from one or more of benzalkonium chloride, benzalkonium bromide and chlorhexidine.
[0023] Preferably, the biguanide antibacterial agent is selected from one or more of polyhexamethyleneguanidine hydrochloride, chlorhexidine, and trifluoromethyldiphenylurea.
[0024] Preferably, the phenolic antibacterial agent is selected from one or more of phenol, m-cresol and xylenol.
[0025] Preferably, the crosslinking agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, epoxy resin, zinc oxide, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and ethylene glycol diacrylate; more preferably, the crosslinking agent is dicumyl peroxide.
[0026] In a second aspect, the present invention also provides a method for preparing the above-mentioned rubber medical composite material, comprising the following steps:
[0027] (1) Preparation of rubber fiber: Rubber is crushed and refined to obtain rubber fiber;
[0028] (2) first dissolving the rubber fiber obtained in step (1) in a solvent, then adding PEEK, a hydroxyapatite biocompatible agent, an antibacterial agent and a cross-linking agent, stirring to mix them evenly to obtain a mixed solution; after stirring and shaking the mixed solution to obtain a polymer, precipitating the polymer;
[0029] (3) freeze-drying the polymer obtained in step (2) to obtain a rubber medical composite material.
[0030] Preferably, the crushing time in step (1) is 20-60 min and the power is 10-15 KW.
[0031] Preferably, in step (2), the solvent in step (2) is selected from one or more of benzene, toluene, xylene, ethylene dichloride, acetone, tetrahydrofuran, pyridine, ethanol, chloroform, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone. More preferably, acetone and xylene are used.
[0032] Preferably, the stirring speed in step (2) is 100-1000 r / min and the time is 2-12 h.
[0033] Preferably, the drying temperature in step (3) is 35-100° C. and the drying time is 8-24 h.
[0034] In a third aspect, the present invention also provides the use of the above-mentioned rubber medical composite material in the preparation of rubber-based composite aerogel.
[0035] In a fourth aspect, a rubber medical composite aerogel comprises the above-mentioned rubber medical composite material.
[0036] In a fifth aspect, the present invention also provides a method for preparing the above-mentioned rubber-based composite aerogel, comprising the following steps:
[0037] The rubber medical composite material is dissolved in other solvents to obtain a composite aerogel, and then the composite aerogel is dried to obtain an aerogel with a porous structure.
[0038] Preferably, in the preparation method, the mass volume ratio of the rubber medical composite material to other solvents is 1 g:3-10 ml, and more preferably, the mass volume ratio is 1 g:4 ml.
[0039] Preferably, other solvents in the preparation method are dioxane, ethyl acetate, and dichloromethane.
[0040] Preferably, the drying technology in the preparation method is supercritical drying technology.
[0041] Preferably, the drying temperature in the preparation method is -100--30°C, more preferably -55°C.
[0042] In a sixth aspect, the present invention also provides the use of the above-mentioned rubber-based composite aerogel in the preparation of medical materials such as antibacterial dressings, drug delivery carriers, cell growth carriers and bone implants.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) As a rubber-based aerogel, it has the advantages of high temperature resistance, radiation resistance, and corrosion resistance, which are its advantages as a high-temperature sterilizable bone tissue implant material. First of all, PEEK itself has good biocompatibility. After combining with magnesium ions, it may further reduce the immune rejection reaction caused by the implant and improve the long-term stability of the implant by promoting cell adhesion, proliferation, and osteoblast differentiation. Secondly, magnesium ions have an osteoinductive effect, which can stimulate the proliferation and differentiation of bone cells and promote the formation of new bones. After combining with PEEK, this osteoinductive effect may be better exerted, which helps to accelerate the repair and healing process of bone defects.
[0045] (2) The present invention is simple to operate and the preparation method is simple, and has the characteristics of low cost and mass production. The rubber-based composite aerogel prepared by the present invention has high porosity, adjustable mechanical strength, good biocompatibility and antibacterial properties. At the same time, the method of the present invention is highly practical and can be applied in the field of medical material engineering technology to achieve large-scale industrial production.
[0046] (3) The preparation method of the present invention can further promote the effective regulation of rubber-based composite aerogel materials. By changing the amount and type of rubber, cross-linking agent, solvent and the proportion of rubber, polyetheretherketone, hydroxyapatite and nano-magnesium oxide, including process optimization, the porosity, pore size, mechanical strength, heat resistance, biocompatibility and antibacterial properties of the aerogel can be changed, so that it can make corresponding changes according to the special requirements of different fields for material properties. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with specific embodiments. The following embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features thereof can be replaced by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0048] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0049] Example 1
[0050] The preparation method of the rubber-based medical composite material comprises the following steps:
[0051] (1) Preparation of rubber fiber: 92 parts of rubber, including 80 parts of medical silicone rubber and 12 parts of natural rubber, were weighed and placed in a crusher for 30 minutes at a power of 12 kW to obtain fine rubber fibers.
[0052] (2) Preparation of rubber medical composite materials: First, add the rubber fiber obtained in step (1) into a dry three-necked flask and add 300 parts of xylene, then add 0.1 parts of diisopropylbenzene peroxide, 4 parts of PEEK powder, 3 parts of HAP powder, and 1 part of nano magnesium oxide to obtain a mixture; mechanically stir the above mixture at a speed of 350 rpm until the rubber is completely dissolved, and stir for 2 hours to allow the system to fully react and allow PEEK to be fully dispersed in the rubber-based solution. Finally, use 200 mL of acetone to precipitate the polymer component in the rubber-based solution. After drying in a vacuum oven at 100°C for 4 hours, a rubber composite powder is obtained.
[0053] Application Example 1
[0054] 50 g of the rubber composite powder prepared in Example 1 was dissolved in 200 mL of dichloromethane solvent and stirred at a speed of 500 r / min for 5 hours to obtain a rubber composite aerogel, which was then freeze-dried in vacuum for 12 hours at a drying temperature of -55°C to obtain an aerogel with a porous structure.
[0055] Application Example 2
[0056] The only difference from Application Example 1 is that 50 g of the rubber compound powder is dissolved in 500 mL of ethyl acetate solvent, and the rest is the same as Application Example 1.
[0057] Application Example 3
[0058] The only difference from Application Example 1 is that 50 g of rubber compound powder is dissolved in 150 mL of dioxane solvent, and the rest is the same as Application Example 1.
[0059] Example 2
[0060] The only difference from Example 1 is that the components and the solvents used in the preparation method are different, PEEK powder is not added, HAP powder is replaced by an equal mass of alumina composite hydroxyapatite powder, diisopropylbenzene peroxide is replaced by an equal mass of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, nano-magnesium oxide is replaced by an equal mass of ketoconazole, and xylene is replaced by an equal mass of benzene.
[0061] The preparation method is the same as that in Example 1.
[0062] Example 3
[0063] The only difference from Example 1 is that the ingredients and the solvents used in the preparation method are different, HAP powder and nano magnesium oxide powder are not added, the medical silicone rubber is replaced by the same mass of polyurethane rubber, the diisopropylbenzene peroxide is replaced by the same mass of epoxy resin, and the xylene is replaced by the same mass of toluene.
[0064] The preparation method is the same as that in Example 1.
[0065] Example 4
[0066] The only difference from Example 1 is that the components and the solvents used in the preparation method are different, HAP powder is replaced by the same mass of calcium alginate composite nano-hydroxyapatite, dicumyl peroxide is replaced by the same mass of zinc oxide, nano-magnesium oxide is replaced by the same mass of octylisothiazolinone, and xylene is replaced by the same mass of ethylene dichloride.
[0067] The preparation method is the same as that in Example 1.
[0068] Example 5
[0069] The only difference from Example 1 is that the ingredients and the solvents used in the preparation method are different, 4 parts of nano magnesium oxide powder are replaced by the same mass of nicotinamide, dicumyl peroxide is replaced by the same mass of trimethylolpropane triacrylate, and xylene is replaced by the same mass of acetone.
[0070] The preparation method is the same as that in Example 1.
[0071] Example 6
[0072] The only difference from Example 1 is that the composition and content of the rubber medical composite material are different and the solvent used in the preparation method is different. The composition of the rubber medical composite material is specifically: 100 parts of rubber (86 parts of medical silicone rubber, 14 parts of natural rubber), 12 parts of polyetheretherketone, 15 parts of HAP powder, 3 parts of zinc thiazole and 0.5 parts of trimethylolpropane trimethacrylate, and xylene is replaced by tetrahydrofuran of the same mass.
[0073] The preparation method is the same as that in Example 1.
[0074] Example 7
[0075] The difference from Example 1 is that the components and component contents of the rubber medical composite material are different and the solvents used in the preparation method are different. The specific components of the rubber medical composite material are: 80 parts of rubber (70 parts of medical silicone rubber, 10 parts of natural rubber), 1 part of polyetheretherketone, 0.1 part of ethylene glycol diacrylate, and xylene is replaced by the same mass of pyridine.
[0076] The preparation method is the same as that in Example 1.
[0077] Example 8
[0078] The only difference from Example 1 is that the antibacterial agent is different and the solvent used in the preparation method is different, specifically: the nano magnesium oxide powder is replaced by the same mass of benzalkonium chloride, and the xylene is replaced by the same mass of dichloromethane.
[0079] Example 9
[0080] The only difference from Example 1 is that the antibacterial agent and the solvent used in the preparation method are different, nano-magnesium oxide is replaced by the same mass of trifluoromethyl diphenyl urea, and xylene is replaced by the same mass of dimethyl sulfoxide.
[0081] Example 10
[0082] The only difference from Example 1 is that the antibacterial agent and the solvent used in the preparation method are different, nano magnesium oxide is replaced by the same mass of m-cresol, and xylene is replaced by the same mass of N,N-dimethylacetamide.
[0083] Embodiment 11
[0084] The only difference from Example 1 is that the solvent used in the preparation method is different, and xylene is replaced by ethanol of the same mass.
[0085] Example 12
[0086] The only difference from Example 1 is that the solvent used in the preparation method is different, and xylene is replaced by the same mass of N,N-dimethylformamide.
[0087] Example 13
[0088] The only difference from Example 1 is that the solvent used in the preparation method is different, and xylene is replaced by N-methylpyrrolidone of the same mass.
[0089] Comparative Example 1
[0090] The only difference from Example 1 is that the medical silicone rubber and purified modified natural rubber in step (1) are replaced by 80 parts of nitrile rubber and 12 parts of purified modified natural rubber to obtain rubber aerogel.
[0091] The preparation method is the same as that in Example 1.
[0092] Comparative Example 2
[0093] The only difference from Example 1 is that the cross-linking agent dicumyl peroxide in step (2) is replaced by benzoyl peroxide to obtain rubber aerogel.
[0094] The preparation method is the same as that in Example 1.
[0095] Comparative Example 3
[0096] The only difference from Example 1 is that no cross-linking agent is added.
[0097] The preparation method is the same as that in Example 1.
[0098] Comparative Example 4
[0099] The only difference from Example 1 is that 0.8 parts of cross-linking agent is added.
[0100] The preparation method is the same as that in Example 1.
[0101] Application Examples
[0102] Preparation of rubber-based aerogels: The rubber composite powders prepared in Examples 2-13 and Comparative Examples 1-4 were respectively used to prepare rubber-based composite aerogels using the method of Application Example 1, to obtain Application Examples 2-13 and Comparative Examples 1-4.
[0103] Effect Experiment
[0104] All application examples 2-13, application comparative examples 1-4 and application example examples 1-3 were respectively used to prepare rubber-based composite aerogels (i.e., application examples 1-13 and application comparative examples 1-4 in the following table) and performance tests were performed, and application example examples 2-4 were also tested for performance (i.e., application example examples 2-4 in the following table). The results are shown in Table 1, and the test method is as follows:
[0105] 1. Porosity measurement
[0106] Since the freeze-dried aerogel structure is a macroporous structure>50nm, the present invention uses a mercury intrusion instrument to measure the porosity, total pore volume, density, average pore size and pore size distribution of the rubber-based composite aerogel. The relevant content is the prior art and will not be repeated here.
[0107] 2. Thermal stability test
[0108] The thermal stability of the aerogel was studied by thermal gradient analysis using a thermogravimetric analyzer under a nitrogen environment at a rate of 10°C / min from 50°C to 800°C. The relevant content is prior art and will not be elaborated here.
[0109] 3. Elastic modulus test
[0110] An electronic universal testing machine was used to perform compression tests to test the elastic modulus of different samples. According to the ASTM guidelines, mechanical compression tests were performed at a rate of 0.05 mm / min at room temperature. When the compression was 60%, the compression modulus was calculated based on the initial slope of the stress-strain curve. The relevant content is prior art and will not be elaborated here.
[0111] 4. Cell proliferation assay
[0112] In order to verify the biocompatibility of this material, the present invention conducted an MTT cytotoxicity experiment. The MTT method is a method for detecting cell survival and growth. MTT is a yellow compound and a dye that accepts hydrogen ions. It can act on the respiratory chain in the mitochondria of living cells. Under the action of succinate dehydrogenase and cytochrome C, exogenous MT is reduced to water-insoluble blue-purple crystalline formazan and deposited in the cells, while dead cells do not have this function. After culturing cells on the substrate for 1 or 3 days, the number of surface cell growth is detected. The relevant content is prior art and will not be repeated here.
[0113] 5. In vitro osteogenic activity assay
[0114] Different samples (three replicates in each group) were inoculated with rat bone marrow mesenchymal stem cells on the surface of 12-well cell culture plates, and cultured to the 7th and 14th days, respectively, for detection. Specifically, 0.5% Triton X-100 was used to break the membrane, the cells were fully blown, centrifuged at 4°C, 1200rpm for 10min, a trace amount of chromogenic substrate was added to an appropriate amount of the supernatant of each sample, 50μL of detection buffer was added, and 100μL of reaction termination solution was added after incubation at 37°C in the dark for 30min, and the absorbance of the final solution at 400nm was measured. Finally, the active alkaline phosphatase activity (ALP) of each sample was calculated, and ALP is an early marker of osteoblast differentiation.
[0115] 6. In vitro antibacterial test
[0116] In order to obtain the antibacterial rate of different samples, 1×10 6 CFU / mL of Escherichia coli and Staphylococcus aureus were inoculated on the sample surface and cultured at 37°C for 24 hours. The bacteria on the sample surface were eluted, collected by ultrasound, and the obtained bacterial solution was diluted with PBS solution to an appropriate multiple, spread on LB solid culture medium, and cultured at 37°C for 18 hours. Finally, take pictures and use software to analyze the antibacterial rate of the samples. The calculation formula is: Antibacterial rate (%) = (CT) / C×100%, C is the average colony count of the rubber aerogel sample, and T is the average colony count of each test group. The experimental results are shown in Table 1 below.
[0117] Table 1
[0118]
[0119]
[0120]
[0121]
[0122] The number of “+” in the table indicates the relative value of biocompatibility. If the biocompatibility value of pure rubber aerogel is “+”, the number of “+” in other embodiments is the value compared with that of pure rubber aerogel.
[0123] The above application examples 1 and application examples 2-13 mainly explore the effects of polyetheretherketone, hydroxyapatite biocompatible agents, and antibacterial agents on the performance of rubber-based aerogels by changing the addition amount of polyetheretherketone / nanomagnesium oxide / hydroxyapatite in rubber, changing the types and preparation conditions of antibacterial agents and crosslinking agents. The addition of polyetheretherketone and hydroxyapatite can increase the compression modulus of rubber-based aerogels, and the high porosity of aerogels makes rubber-based composite aerogels a substitute for bone implant materials. Among them, the aerogel obtained by the component ratio and preparation method of application example 1 is the best.
[0124] It can be seen from the application comparative example 1 that the porosity, biocompatibility and antibacterial rate of the rubber-based aerogel obtained by combining medical silicone rubber and natural rubber are better than those of the rubber-based aerogel obtained by combining polyurethane rubber and natural rubber.
[0125] It can be seen from the comparative example 2 that the porosity, biocompatibility and antibacterial rate of the rubber-based aerogel obtained by using dicumyl peroxide as the crosslinking agent are better than those of the rubber-based aerogel obtained by using benzoyl peroxide as the crosslinking agent. Therefore, the crosslinking agent is within the scope of the present invention, and the effect is better.
[0126] It can be seen from the comparative examples 3 and 4 that the crosslinking agent and the amount of the crosslinking agent added must be within the range of the present invention to achieve the best effect.
[0127] Therefore, the present invention can adjust the porosity, pore size, mechanical strength, heat resistance, osteogenicity, biocompatibility and antibacterial properties of the aerogel by changing the proportions of rubber, polyetheretherketone, hydroxyapatite, nano-magnesium oxide, and cross-linking agent as well as the preparation conditions, and corresponding changes can be made according to the requirements for material properties.
Claims
1. A rubber medical composite material, characterized in that: The rubber medical composite material comprises the following components by weight: 80-100 parts of rubber, 0-12 parts of polyetheretherketone, 0-15 parts of hydroxyapatite biocompatibility agent, 0-3 parts of antibacterial agent and 0.1-0.5 parts of cross-linking agent; wherein the polyetheretherketone, hydroxyapatite biocompatibility agent and antibacterial agent are not 0 at the same time.
2. The rubber medical composite material according to claim 1, characterized in that: The rubber is selected from one or more of purified modified natural rubber, medical silicone rubber and polyurethane rubber; The hydroxyapatite biocompatible agent is selected from one or more of hydroxyapatite, alumina composite hydroxyapatite and calcium alginate composite nano-hydroxyapatite; The antibacterial agent is selected from one or more of oxide antibacterial agents, diammonium phosphate inorganic antibacterial agents, acylanilide antibacterial agents, imidazole antibacterial agents, thiazole antibacterial agents, isothiazolone derivative antibacterial agents, quaternary ammonium salt antibacterial agents, bis-quaternary antibacterial agents and phenolic antibacterial agents; The crosslinking agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, epoxy resin, zinc oxide, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and ethylene glycol diacrylate.
3. The method for preparing the rubber medical composite material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of rubber fiber: Rubber is crushed and refined to obtain rubber fiber; (2) first dissolving the rubber fiber obtained in step (1) in a solvent to prepare a rubber fiber solution, then adding polyetheretherketone, hydroxyapatite biocompatible agent, antibacterial agent and cross-linking agent, and then stirring to mix them evenly to obtain a mixed solution; after stirring and shaking the mixed solution to obtain a polymer, precipitating the polymer; (3) freeze-drying the polymer obtained in step (2) to obtain a rubber medical composite material.
4. The preparation method according to claim 3, characterized in that: The solvent in step (2) is selected from one or more of benzene, toluene, xylene, dichloroethane, acetone, tetrahydrofuran, pyridine, ethanol, dichloromethane, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
5. Use of the rubber medical composite material according to claim 1 or 2 in preparing rubber medical composite material aerogel.
6. A rubber medical composite aerogel, characterized in that: The medical rubber composite material comprises the rubber medical composite material according to claim 1 or 2.
7. The method for preparing the rubber medical composite aerogel according to claim 6, characterized in that: The method comprises the following steps: dissolving the rubber medical composite material according to any one of claims 1 or 2 in other solvents to obtain a composite aerogel; and drying the composite aerogel to obtain an aerogel with a porous structure.
8. The preparation method according to claim 7, characterized in that: The other solvents are selected from one or more of dioxane, ethyl acetate and dichloromethane.
9. The preparation method according to claim 7, characterized in that: The mass volume ratio of the rubber medical composite material to other solvents is 1g:3-10ml.
10. Use of the rubber medical composite aerogel according to claim 6 or the rubber medical composite aerogel prepared by the preparation method according to any one of claims 7 to 9 in the preparation of medical materials such as antibacterial dressings, drug delivery carriers, cell growth carriers and bone implants.
Citation Information
Patent Citations
Interbody fusion deVice based on 3D printing and preparation method of deVice
CN108670505A